Ross Poldark [compact disc, unabridged] : a novel of Cornwall, 1783-1787 - Graham, Winston (Random House Audio, 2015)
Ross Poldark returns to Cornwall from war, looking forward to a joyful homecoming with his family and his beloved Elizabeth. But instead he discovers that his father has died, his home is overrun by livestock and drunken servants, and Elizabeth, having believed Ross dead, is now engaged to his cousin. Ross must start over, building a completely new path for his life, one that takes him in exciting and unexpected directions.